2001
DOI: 10.1094/phyto.2001.91.6.565
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Molecular Characterization of a New Cucurbit-Infecting Tobamovirus

Abstract: An uncharacterized virus was isolated from greenhouse-grown cucumber plants. Biological and serological data described in the present study indicated that the virus belonged in the genus Tobamovirus. The host range of the virus included several plant species within the family Cucurbitaceae. The virus designated Cucumber fruit mottle mosaic virus (CFMMV) causes severe mottling or mosaic on cucumber fruits, and its fast spread within greenhouses could lead to significant economic losses in cucumber crops. The ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
46
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 26 publications
2
46
0
Order By: Relevance
“…A survey of literature on virus diseases of cucurbits revealed that more than 39 well characterized viruses are distributed in unrelated genera, such as Begomo virus, Crinivirus, Cucumovirus, Polerovirus, Tospovirus, Ipomovirus, Tobamovirus and Potyvirus, which are known to naturally infect cucurbits (Antignus et al, 2001;Salem et al, 2007;Kneirim et al, 2010;Gholamalizadeh et al, 2008;Brown et al, 2002;Owolabi et al, 2008Owolabi et al, , 2011Owolabi et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…A survey of literature on virus diseases of cucurbits revealed that more than 39 well characterized viruses are distributed in unrelated genera, such as Begomo virus, Crinivirus, Cucumovirus, Polerovirus, Tospovirus, Ipomovirus, Tobamovirus and Potyvirus, which are known to naturally infect cucurbits (Antignus et al, 2001;Salem et al, 2007;Kneirim et al, 2010;Gholamalizadeh et al, 2008;Brown et al, 2002;Owolabi et al, 2008Owolabi et al, , 2011Owolabi et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Among those detection methods, RT-PCR (Ugaki et al, 1991;Shim et al, 2005;Yoon et al, 2008;Liu et al, 2009), real time RT-PCR (Chen et al, 2008, transmission electron microcopy (Alshahwan and Abdalla, 1992), immune capture-RTPCR (Celix et al, 1996), ELISA (Antignus et al, 1990;Celix et al, 1996;Mitsuhiro et al, 2006) and monoclonal antibodies (Antignus et al, 2001). To establish procedure of identification and detection, mechanical inoculation, DAS-ELISA, RT-PCR, molecular hybridization and nucleotide sequence were applied in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Precise diagnosis has the prime importance in developing a management strategy of this virus. All these viruses have similar host range and thus cannot be used as a clue for the identification of the virus (Antignus et al, 2001;Yoon et al, 2002). CGMMV was originally described in the UK 1935 (Ainsworth, 1935).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Crop yield losses of about 15% have been reported (1,2). CGMMV contains a 6.4 kb (+) ssRNA genome (6).…”
mentioning
confidence: 99%